Image quality improvement in a hard X-ray projection microscope using total reflection mirror optics - Mimura, Hidekazu (Journal of synchrotron radiation, 2004)
A new figure correction method has been applied in order to fabricate an elliptical mirror to realize a one-dimensionally diverging X-ray beam having high image quality. Mutual relations between figure errors and intensity uniformities of diverging X-ray beams have also been investigated using a wave-optical simulator and indicate that figure errors in relatively short spatial wavelength ranges lead to high-contrast interference fringes. By using a microstitching interferometer and elastic emission machining, figure correction of an elliptical mirror with a lateral resolution close to 0.1 mm was carried out. A one-dimensional diverging X-ray obtained using the fabricated mirror was observed at SPring-8 and evaluated to have a sufficiently flat intensity distribution